Primary Angiitis of the Central Nervous System Mimicking Glioblastoma: A Case Report and Literature Review - Jin, Hang; Qu, Yang; Guo, Zhen-Ni; Cui, Guo-Zhen; Zhang, Fu-Liang; Yang, Yi (Frontiers in Neurology, 2019)
Primary angiitis of the central nervous system (PACNS) is a rare disorder resulting in idiopathic inflammation affecting the parenchymal and leptomeningeal vessels confined to the central nervous system (CNS), of which a tumor-like mass lesion is an even rare subtype. We described a case of PACNS initially misdiagnosed as glioblastoma. The patient was a 35-year-old female with right-sided weakness and expressive dysphasia. Brain MRI showed a tumor-like lesion highly suggestive of glioblastoma, therefor surgical removal was done. After a resection and an exhaustive workup, PACNS was ultimately diagnosed. The case illustrates a type of imaging presentation of PACNS that is often misdiagnosed as high-grade glioma. Differentiation between tumor-like PACNS lesions and actual CNS tumors is challenging due to similar MR images. To avoid unnecessary surgical interventions, we summarized previously reported mass-forming PACNS cases in adults from January 1, 2000, to December 31, 2018 and the imaging characteristics of PACNS. Some less commonly used diagnostic methods such as MR spectroscopy may also help clinicians distinguish PACNS from its mimics.